An Audit of Injuries Sustained in Two–Wheeler Accidents in the Metropolitan City of Karachi, Pakistan - Farzana azam khan, ramlah naz, mehreen fatima, s. Zubair ahmed tarmizi, qarar abbasi, adina anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Road traffic accidents have major contribution in injury related mortality and disability in low income countries. Two-wheelers being a major mode of transportation due to absence of proper public transport system in Karachi hence most often reported accidents are related with two wheelers. In Karachi two wheelers are quite commonly being used as mode of transportation, number of two wheelers has increased to 10 folds since last 10 years because of lack of public transports and high fuel prices and easy availability on low monthly instalments. Objective: To analyze the injury pattern among two-wheeler riders in Karachi. Study Design: Retrospective study Place and Duration of Study: Three major medico-legal centres of Karachi (Civil, Jinnah, and Abbasi Shaheed Hospitals) from 1st January 2017 to 31st December 2021. Methodology: About 11444 two-wheeler incidents occurred on roads with the consent of Police Surgeon Office Karachi were enrolled. The patients’ demographics, injuries sustained, date of the injuries, cause of the injuries, types of collision and outcomes were recorded. Results: Most of the riders engaged in accidents were between the ages of 18 and 30 years; 90.99% of the riders were men. The most frequent type of injuries found in two wheeler accidents were abrasions/grazes seen in (56.26%) cases followed by fractures (20.82%), head injuries (11.02%). Conclusion: Greater prevalence in the age group of 18-30 years, with male dominance analyzed. Fatal and non-fatal injuries were observed. Metro services mass transit programme to be encouraged so to decrease the traffic on road which will automatically reduce the number of accidents to wheeler as well as pillion riders strict efforts need to be made at both government and personal levels to reduce accidents in two-wheeler riders Keyword: Riders, Pillion, Road traffic accidents